Inflammatory prognostic index is a new predictive marker for perioperative mortality in patients undergoing type A aortic dissection surgery - Serdar Badem; Mustafa Selcuk Atasoy (Turkish Journal of Vascular Surgery)
Aim: This study aimed to investigate the potential predictive value of the inflammatory prognostic index (IPI) on perioperative mortality in patients undergoing type A aortic dissection (TAAD) surgery. Material and Methods: A total of 111 patients who underwent TAAD surgery between July 2019 and October 2023 were evaluated. The patients were divided into two groups; mortality group (n=33) and survivor group (n=78). The independent predictors of perioperative mortality were identified using multivariate logistic regression analysis, and the cut-off values of mortality predictors were identified using a ROC curve. Results: The mean ages were 66.4±12.1 and 58.8±11.0 years in the mortality and survivor groups, respectively, and the difference between the groups was statistically significant. Median cardiopulmonary bypass duration, postoperative cerebrovascular event rates, and bleeding requiring revision were significantly higher in the mortality group, while the median lengths of intensive care unit and hospital stay were significantly lower. Mean values of neutrophils, neutrophils/lymphocytes, red blood cell distribution width, mean platelet volume, C-reactive protein, creatinine, and IPI were significantly higher in the mortality group, while lymphocytes, platelet distribution width, glomerular filtration rate, and albumin were lower. Age, neutrophils, and IPI were found to be independent predictors of mortality using logistic regression analysis. An ideal cut-off value of 1.98 for IPI with 84.8% sensitivity and 85.9% specificity was determined using ROC curve analysis (AUC=0.943, 95% CI=0.899-0.986). Conclusion: This study demonstrated that high IPI levels significantly and independently predicted perioperative mortality in TAAD patients. [Turk J Vasc Surg 2025; 34(1.000): 25-32]